Building Trust in the State with Information : Evidence from Urban Punjab - Khan, Adnan; Nasim, Sanval; Shaukat, Mahvish; Stegmann, Andreas (World Bank, Washington, DC, 2020)
Can communication designed to increase support for government policy and shift perceptions of state capacity redress deep-rooted mistrust in state institutions? This paper finds providing information on past state effectiveness, highlighting citizens' cooperation in enabling past effectiveness or appealing to religious authorities' support for government policy have limited impact on support for policy, perceptions of state capacity and trust in the state in Pakistan. This holds true on average and across important dimensions of heterogeneity after accounting for experimenter demand. This paper highlights the limits of using information to build trust in state institutions, and the importance of measuring experimenter demand.